Persepsi Masyarakat tentang Pembentukan Karakter Siswa pada Sekolah Katolik di Ambarawa - Rininta Cintya Sari; Budi Hartana; Adi Wasito (Perkumpulan Perguruan Tinggi Agama Katolik Indonesia, 2023)
Catholic schools are required to have unique character building programs for their students. Character education in Catholic schools is a continuous combination of hard and soft skills building. These two directions of development give students intellectual intelligence and form self-integrity as individuals with strong character. In education, this demand cannot be separated from moral responsibility and competition among the educational instititutions. This competition raises various problems, including the closing down of schools due to various problems. As the phenomenon described in Ambarawa, several Catholic schools had to close down due to the absence of students. This problem is, of course, related to the community's perception of the peculiarities of Catholic schools in character building. This study examines people's perceptions of character-building in Catholic schools. This study uses a descriptive quantitative method with participants, namely the general public who live in Ambarawa City and its surroundings. The results showed that people's perceptions of character building at Catholic schools in Ambarawa were classified as high 70.59%, very high 26.89%, moderate 1.68%, low 0%, and very low 0.84%. The study results show that the public perceives Catholic schools as schools with a clear and visionary education system. The results of this study can be used as evaluation material for policymakers in developing Catholic schools in Ambarawa and its surroundings.